Synthesis and self-assembly study of zwitterionic amphiphilic derivatives of chitosan - Goncalves Barbosa, Hellen Franciane [UNESP]; Furuyama Lima, Aline Margarete [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Fernandes, Julio Cesar; Oliveira Tiera, Vera Aparecida de [UNESP]; Tiera, Marcio Jose [UNESP] (Wiley-Blackwell, 2016)
New zwitterionic derivatives of chitosan (CH) were synthesized through the Michael addition reaction of 1-(3-sulfopropyl)2-vinylpyridine hydroxide (SPP) with primary amines of deacetylated CHs (with weight-average molecular weights of 46 and 216 kDa) to obtain SPP-substituted CHs. The hydrophilic derivatives were subsequently modified with 2.1, 4.6, and 9.7% of dodecyl groups [degree of substitution by dodecyl groups (DSDod)]. The SPP-substituted CH derivatives were characterized by H-1-NMR, Fourier transform infrared spectroscopy, and gel permeation chromatography. Aqueous solutions of SPP-substituted CH samples remained clear, independently of the pH (3.0< pH< 12.0). The self-association study of the amphiphilic derivatives was performed in aqueous buffered solution at pH 5.0 and 7.4, and the critical aggregation concentration values varied from 5.6 x 10(-3) to 0.02 g/L. The measurements of dynamic light scattering and zeta potentials showed that the self-assembly behavior was dependent on the pH and DSDod. At pH 7.4, the measured zeta potentials were near zero, and colloidal stability was provided by the hydrated zwitterionic shell of the aggregates. Transmission electron microscopy revealed spherelike microsized particles of broad distribution. The amphiphilic SPP-substituted CH samples were shown to be nontoxic with a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay performed with HeLa cells. The remarkable water solubility and nontoxicity displayed by the new SPP-substituted CH derivatives showed promising properties for the design of CH-based biomaterials and nanoparticles. (C) 2016 Wiley Periodicals, Inc.
Keywords: biopolymers and renewable polymers; colloids; drug-delivery systems; polysaccharides; self-assembly